Experimental band structure spectroscopy along a synthetic dimension - Avik Dutt (Nature Portfolio, 2019)
Internal degrees of freedom allow to expand the effective dimensionality of a system along “synthetic” dimensions. Here, the authors demonstrate this by modulating a ring resonator at frequencies commensurate with its mode spacing, and are able to directly measure its synthetic band structure.